2020
DOI: 10.7717/peerj.8695
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of root-associated culturable fungi ofCephalanthera rubra(Orchidaceae) in relation to soil characteristics

Abstract: Cephalanthera rubra (L.) Rich., Red Helleborine, is a widespread orchid in Europe but known only from three very small populations in England. These populations are in decline with no natural seed setting for more than a decade. The species may become extinct in the UK soon unless viable strategies are in place for ex situ conservation, especially the use of symbiotic propagation. Because of the fragile nature of the populations in England mycorrhizal fungal diversity study is not feasible. Therefore, to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Previous studies have demonstrated the importance of in vitro fungal isolation in the understanding and experimenting on OM. Moreover, the identifications of some relatively easy-toisolate strains and biological effect detection have been reported in recent years (Meng et al, 2019a,b,c;Bell et al, 2020;Gao et al, 2020b;Zhang et al, 2020). Isolation methods mainly include isolation from whole tissue or tissue section, in situ seeding and trapping isolation, and single peloton isolation; of these, single peloton isolation (i.e., the isolation of pelotons from host cells by micromanipulation) is considered as the most reliable and accurate method (Zettler et al, 2005;Batty et al, 2006;Zi et al, 2014;Zettler and Corey, 2018).…”
Section: Research Methods Of Orchid-fungal Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the importance of in vitro fungal isolation in the understanding and experimenting on OM. Moreover, the identifications of some relatively easy-toisolate strains and biological effect detection have been reported in recent years (Meng et al, 2019a,b,c;Bell et al, 2020;Gao et al, 2020b;Zhang et al, 2020). Isolation methods mainly include isolation from whole tissue or tissue section, in situ seeding and trapping isolation, and single peloton isolation; of these, single peloton isolation (i.e., the isolation of pelotons from host cells by micromanipulation) is considered as the most reliable and accurate method (Zettler et al, 2005;Batty et al, 2006;Zi et al, 2014;Zettler and Corey, 2018).…”
Section: Research Methods Of Orchid-fungal Diversitymentioning
confidence: 99%
“…Currently, in vitro investigations on the functions of ONF during the life cycle of orchids are limited, even though at least 65 ONF genera have been successfully isolated and cultured (Novotná et al, 2018;Meng et al, 2019a,b,c;Sarsaiya et al, 2019;Shah et al, 2019;Bell et al, 2020). It is crucial to further investigate the ONF that frequently occurs in orchids roots, in order to determine their potential physiological and ecological advantages.…”
Section: Orchid Non-mycorrhizal Fungal Diversitymentioning
confidence: 99%
“…had high diversity (H and D indices) for non-mycorrhizal fungi when P content was high and K content was low. As Bell et al [ 40 ] reported with Cephalanthera rubra , members of Cynorkis also recruited more non-mycorrhizal fungi when soil P values were comparatively high. The Central Highlands landscape is prone to eutrophication due to burning and grazing.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, for the purpose of understanding specific requirements for reintroduction, targeted environmental analysis is required. Previous studies indicate that low P content may be linked to higher mycorrhizal diversity in Cephalanthera rubra [ 40 ] and several orchids from Madagascar [ 11 ]. Likewise, Van der Ent et al [ 41 ] found that the rhizosphere soil concentrations of P and K was low in soil in the study site where Paphiopedilum rothschildianum was growing.…”
Section: Discussionmentioning
confidence: 99%
“…Talaromyces , Alternaria , Exophiala , Cyphellophora , Cladosporium , Phialophora , Xylaria ) have also been isolated and identified in numerous other plants (e.g. Bonfim et al ., 2016; Liu et al ., 2017; Bell et al ., 2020). In addition, Alternaria sp., Cyphellophora sp., Exophiala dermatitis and Paraconiothyrium sp.…”
Section: Discussionmentioning
confidence: 99%